2020
DOI: 10.1111/1758-2229.12837
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic carbon fixation pathways along the redox gradient in oxygen‐depleted oceanic waters

Abstract: Anoxic marine zones (AMZs), also known as 'oxygendeficient zones', contribute to the loss of fixed nitrogen from the ocean by anaerobic microbial processes. While these microbial processes associated with the nitrogen cycle have been extensively studied, those linked to the carbon cycle in AMZs have received much less attention, particularly the autotrophic carbon fixationa crucial component of the carbon cycle. Using metagenomic and metatranscriptomic data from major AMZs, we report an explicit partitioning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…By further investigation on pathway level 3, several functions were confirmed to be more abundant in water column below 90 m; for example, Pyruvate metabolism, Glyoxylate and dicarboxylate metabolism, amino sugar and nucleotide sugar metabolism and butanoate metabolism (affiliated to carbohydrate metabolism), carbon fixation pathways in prokaryotes (affiliated to energy metabolism), homologous recombination (affiliated to replication and repair), bacterial secretion system (affiliated to membrane transport), flagellar assembly and bacterial chemotaxis (affiliated to cell motility), and biofilm formation – Vibrio cholerae (affiliated to cellular community – prokaryotes). The results confirmed the vital processes of carbon and nutrient cycling in the anoxic environment in the deep blue hole (Ruiz‐Fernández et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…By further investigation on pathway level 3, several functions were confirmed to be more abundant in water column below 90 m; for example, Pyruvate metabolism, Glyoxylate and dicarboxylate metabolism, amino sugar and nucleotide sugar metabolism and butanoate metabolism (affiliated to carbohydrate metabolism), carbon fixation pathways in prokaryotes (affiliated to energy metabolism), homologous recombination (affiliated to replication and repair), bacterial secretion system (affiliated to membrane transport), flagellar assembly and bacterial chemotaxis (affiliated to cell motility), and biofilm formation – Vibrio cholerae (affiliated to cellular community – prokaryotes). The results confirmed the vital processes of carbon and nutrient cycling in the anoxic environment in the deep blue hole (Ruiz‐Fernández et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our current knowledge of the nitrogen, sulfur, and oxygen cycles in OMZs (Ganesh et al, 2014;Ganesh et al, 2015;Glass et al, 2015;Garcia-Robledo et al, 2016;Garcia-Robledo et al, 2017;Fuchsman et al, 2017;Saunders et al, 2019;Raven et al, 2021), the carbon cycle has been poorly characterized in these low-oxygen environments. Recently couplings between carbon, sulfur, and nitrogen metabolisms have been proposed (Plominsky et al, 2018), along with the partitioning of different carbon fixation pathways along the AMZ redox gradient (Ruiz-Fernańdez et al, 2020). Considering all the caveats regarding metatranscriptomic fragment recruitment, the data presented here suggests an in situ coupling of Alteromonas iron and carbon metabolisms and the potential importance of its glyoxylate cycle in the AMZs.…”
Section: Discussionmentioning
confidence: 71%
“…The reductive acetyl-CoA pathway was found to be the most abundant carbon fixation pathway in deep biosphere (41, 42), however, our results suggested that this pathway does not work for the microorganisms in Bamucuo. The 3-hydroxypropionate/4-hydroxybutyrate cycle and the dicarboxylate/4-hydroxybutyrate cycle pathways existed in thermophilic archaea, however, Ruiz-Fernandez et al concluded that the 3-hydroxypropionate/4-hydroxybutylate cycle is the dominant pathway in anoxic marine zones (43). Obviously, their conclusion is different from ours.…”
Section: Discussionmentioning
confidence: 99%
“…3b). The top three GO terms were as follows: cellular process (45,113), metabolic process (43,200) and response to stimulus (12,611) among the biological processes; catalytic activity (35,860), binding (24,853) and structural molecule activity (4,247) among the molecular functions; and cell (45,101), cell part (45,101) and membrane (19,524) among the cellular components.…”
Section: Introductionmentioning
confidence: 99%